2022
DOI: 10.1002/jlb.4cova0122-076r
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell immune profiling reveals long-term changes in myeloid cells and identifies a novel subset of CD9+ monocytes associated with COVID-19 hospitalization

Abstract: Coronavirus disease 2019 (COVID‐19) caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection can result in severe immune dysfunction, hospitalization, and death. Many patients also develop long‐COVID‐19, experiencing symptoms months after infection. Although significant progress has been made in understanding the immune response to acute SARS‐CoV‐2 infection, gaps remain in our knowledge of how innate immunity influences disease kinetics and severity. We hypothesized that cytometry by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
2
1
0
Order By: Relevance
“…While no difference in major inflammatory cytokines between the three groups was observed, correlations of CD169 + monocyte subsets with cytokines suggested that specific activated monocyte subsets produce high levels of proinflammatory cytokines in PPASC. Correlations of D-dimer with CD169 + non-classical monocytes observed herein were corroborated by the findings of Pandori et al (2022) in a cohort of individuals hospitalized for COVID-19 38 . Interestingly, their cohort did not display the increases in total monocyte populations in their hospitalized group but displayed decreases in non-classical monocyte percentages and steady levels of classical and intermediate monocyte percentages from total CD45 + cells in participants hospitalized for COVID-19 up to 90 days following admission.…”
Section: Discussionsupporting
confidence: 91%
“…While no difference in major inflammatory cytokines between the three groups was observed, correlations of CD169 + monocyte subsets with cytokines suggested that specific activated monocyte subsets produce high levels of proinflammatory cytokines in PPASC. Correlations of D-dimer with CD169 + non-classical monocytes observed herein were corroborated by the findings of Pandori et al (2022) in a cohort of individuals hospitalized for COVID-19 38 . Interestingly, their cohort did not display the increases in total monocyte populations in their hospitalized group but displayed decreases in non-classical monocyte percentages and steady levels of classical and intermediate monocyte percentages from total CD45 + cells in participants hospitalized for COVID-19 up to 90 days following admission.…”
Section: Discussionsupporting
confidence: 91%
“…Correlations of D-dimer with CD169 + non-classical monocytes observed herein were corroborated by the findings of Pandori et al. ( 39 ) in a cohort of individuals hospitalized for COVID-19 ( 39 ). Interestingly, their cohort did not display the increases in total monocyte populations in their hospitalized group but displayed decreases in non-classical monocyte percentages and steady levels of classical and intermediate monocyte percentages from total CD45 + cells in participants hospitalized for COVID-19 up to 90 days following admission.…”
Section: Discussionsupporting
confidence: 90%
“…At the same time, no institutions were founded for platelet-to-lymphocyte ratio (PLR). 17 , 18 , 20 , 21 , 23 27 …”
Section: Introductionmentioning
confidence: 99%